Modern views on the epidemiology, etiology and pathogenesis of gynecomastia - Yu. N. Yashina; R. V. Rozhivanov; D. G. Kurbatov (Андрология и генитальная хирургия, 2014)
The review deals with one of the pressing andrological issues – gynecomastia, its etiology and pathogenesis. Based on the current epidemiological and experimental data, most common etiological factors of gynecomastia were investigated. A multiple-valued role of various causes of gynecomastia in several age-groups was revealed. Literature data show that gynecomastia may be a manifestation of various diseases: endocrine, genetic, systematic. As well as that, gynecomastia may occur in patients with oncological diseases. However, gynecomastia can be an iatrogenic complication. Currently, we continue to make insights to the problem of gynecomastia in order to be able to classify its etiological factors and determine its basic pathogenesis pathways.